Evaluation of antimicrobial activity and in vitro safety of the methanolic extract of Streptomyces manipurensis soil isolate H21 for potential industrial applications - Yomna N. Elkholy; Walid Faisal Elkhatib; Khaled M. Aboshanab; Mohammad Aboulwafa; Nadia A. Hassouna (Ain Shams University, 2019)
Streptomyces manipurensis isolate H21 was recovered from a soil sample in Cairo, Egypt. Cell-free culture supernatant of Streptomyces manipurensis isolate H21 previously showed antifungal and broad-spectrum antibacterial activity against some Gram-positive, Gram-negative, MDR, and ESBL producer pathogens as well as some reference strains. The present study aimed at investigating antimicrobial and cytotoxic activities of its crude methanolic extract. The antibacterial activity of the crude methanolic extract was determined using broth-dilution method against Staphylococcus aureus ATCC 43300, Klebsiella oxytoca ATCC 700324, Klebsiella pneumoniae ATCC 700603, Klebsiella pneumoniae ATCC BAA-1705 and 2 MDR uropathogens. The minimum inhibitory concentrations (MICs) and the minimum bactericidal concentrations (MBCs) of the crude extract against the tested bacteria were in the range of 5-10 mg/mL and 10 mg/mL, respectively. The results revealed that the CD50 value of the extract was 1.17 mg/mL, against Caco-2 cell line, indicating in vitro safety and low cytotoxicity. Accordingly, Streptomyces manipurensis isolate H21 would be an excellent source of relatively safe and potent antibacterial agent.